Maternal and fetal characteristics for predicting risk of Cesarean section following induction of labor: pooled analysis of PROBAAT trials. (5th January 2022) - Quach, D.; ten Eikelder, M.; Jozwiak, M.; Davies‐Tuck, M.; Bloemenkamp, K. W. M.; Mol, B. W.; Li, W.
ABSTRACT: Objective: Induction of labor (IOL) is one of the most widely used obstetric interventions. However, one‐fifth of IOLs result in Cesarean section (CS). We aimed to assess maternal and fetal characteristics that influence the likelihood of CS following IOL, according to the indication for CS. Methods: This was a secondary analysis of pooled data from four randomized controlled trials, including women undergoing IOL at term who had a singleton pregnancy and an unfavorable cervix, intact membranes and the fetus in cephalic presentation. The main outcomes of this analysis were CS for failure to progress (FTP) and CS for suspected fetal compromise (SFC). Restricted cubic splines were used to determine whether continuous maternal and fetal characteristics had a non‐linear relationship with outcome. Optimal cut‐offs for those characteristics with a non‐linear pattern were determined based on the maximum area under the receiver‐operating‐characteristics curve. Adjusted odds ratios (aOR) were computed, using multivariable logistic regression analysis, for the associations between optimally categorized characteristics and outcome. Results: Of a total of 2990 women undergoing IOL, 313 (10.5%) had CS for FTP and 227 (7.6%) had CS for SFC. The risk of CS for FTP was increased in women aged 31–35 years compared with younger women (aOR, 1.51 (95% CI, 1.15–1.99)), in nulliparous compared with parous women (aOR, 8.07 (95% CI, 5.34–12.18)) and in Sub‐Saharan African compared with Caucasian women (aOR, 2.09 (95% CI, 1.33–3.28)). Higher body mass index (BMI) increased incrementally the risk of CS for FTP (aOR, 1.06 (95% CI, 1.04–1.08)). High birth‐weight percentile was also associated with an increased risk of CS due to FTP (aOR, 2.66 (95% CI, 1.74–4.07) for birth weight between the 80.0 th and 89.9 th percentiles and aOR, 4.08 (95% CI, 2.75–6.05) for birth weight ≥ 90 th percentile, as compared with birth weight between the 20.0 th and 49.9 th percentiles). For CS due to SFC, higher maternal age (aOR, 1.09 (95% CI, 1.05–1.12)) and BMI (aOR, 1.05 (95% CI, 1.03–1.08)) were associated with an incremental increase in risk. The risk of CS for SFC was increased in nulliparous compared with parous women (aOR, 5.91 (95% CI, 3.76–9.28)) and in South Asian compared with Caucasian women (aOR, 2.50 (95% CI, 1.23–5.10)). Birth weight < 10.0 th percentile increased significantly the risk of CS due to SFC (aOR, 1.93 (95% CI, 1.22–3.05)), as compared with birth weight between the 20.0 th and 49.9 th percentiles. Bishop score did not demonstrate a significant association with the risk of CS for FTP or for SFC. Conclusions: In women undergoing IOL, maternal age, BMI, parity, ethnicity and birth‐weight percentile are predictors of CS due to FTP and of CS due to SFC, but the direction and magnitude of the associations differ according to the indication for CS. These characteristics should be considered in combination with the Bishop score to stratify the risk of CS for different indications in women undergoing IOL. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.